Unusual Cause of Headache in Childhood: Giant Quadrigeminal Cistern Arachnoid Cyst - Inci, M. F.; Ozkan, F.; Demir, C. F.; Vurdem, U. E. (Medcom Ltd, 2013)
Quadrigeminal cistern arachnoid cyst (QAC) is the third most common posterior fossa arachnoid cysts of childhood if middle fossa arachnoid cysts are excluded. These cavities are believed to be congenital and patients usually present with headache, nausea, vomiting, hearing loss, dizziness, behavioural disturbances and psychomotor retardation. QACs are localised between the collicules and cerebellum is usually compressed inferiorly. A 30-month-old boy was referred with vomiting and headache. There was no report of recent associated infections, previous history of any classical childhood viral infection or alterations of psychomotor development. Magnetic resonance imaging showed a large supratentorial arachnoid cyst in the quadrigeminal cistern displacing the brainstem inferiorly and extending anterolaterally into the prepontine cisterns.
Keywords: Arachnoid cyst; Quadrigeminal cistern; Magnetic resonance imaging